Structure-Based Drug Design of ADRA2A Antagonists Derived from Yohimbine - Chayka, Artem; Česnek, Michal; Kužmová, Erika; Kozák, Jaroslav; Tloušt'ová, Eva; Dvořáková, Alexandra; Strmeň, Timotej; Brož, Břetislav; Osifová, Zuzana; Dračínský, Martin; Mertlíková-Kaiserová, Helena; Janeba, Zlatko (Journal of medicinal chemistry, 2024)
Yohimbine, a natural indole alkaloid and a nonselective adrenoceptor antagonist, possesses potential benefits in treating inflammatory disorders and sepsis. Nevertheless, its broader clinical use faces challenges due to its low receptor selectivity. A structure-activity relationship study of novel yohimbine analogues identified amino esters of yohimbic acid as potent and selective ADRA2A antagonists. Specifically, amino ester 4n, in comparison to yohimbine, showed a 6-fold higher ADRA1A/ADRA2A selectivity index (SI > 556 for 4n) and a 25-fold higher ADRA2B/ADRA2A selectivity index. Compound 4n also demonstrated high plasma and microsomal stability, moderate-to-low membrane permeability determining its limited ability to cross the blood-brain barrier, and negligible toxicity on nontumor normal human dermal fibroblasts. Compound 4n represents an important complementary pharmacological tool to study the involvement of adrenoceptor subtypes in pathophysiologic conditions such as inflammation and sepsis and a novel candidate for further preclinical development to treat ADRA2A-mediated pathologies.
Keywords: yohimbin; Animals; alfa-2-adrenergní receptory - antagonisté; racionální návrh léčiv; Structure-Activity Relationship; lidé; Drug Design; Yohimbine; alfa-2-adrenergní receptory; vztahy mezi strukturou a aktivitou; Adrenergic alpha-2 Receptor Antagonists; Humans; zvířata; Receptors, Adrenergic, alpha-2